IRRITANTCY POTENTIAL AND SUB ACUTE DERMAL TOXICITY STUDY OF PISTACIA LENTISCUS FATTY OIL AS A TOPICAL TRADITIONAL REMEDY. - DJERROU, Zouhir; Djaalab, Hadria; Riachi, Foulla; Serakta, Mennouba; Chettoum, Aziez; Maameri, zineb; Boutobza, Badaoui; Hamdi Pacha, Youcef (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The current study was undertaken to assess safety of Pistacia lentiscus fruits fatty oil (PLFO) as a topical traditional remedy. A primary skin and eye irritation tests were conducted with New Zealand white rabbits to determine the potential for PLFO to produce irritation from a single application. In addition, a sub acute dermal toxicity study was performed on 18 NZW rabbits to evaluate possible adverse effect following application of PLFO for 28 days. Based on the results of the current study, PLFO is classified as slightly irritating to the skin and the eye of rabbits (Primary Irritation Index (P.I.I.) = 1.037; ocular irritation index (O.I.I.) = 5.33 at 1 h). In the sub acute toxicity test, PLFO produced neither mortality nor significant differences in the body and organ weights between control group and treated rabbits. However, a reversible irritant contact dermatitis was observed in the treated areas since the end of the second week of application until the end of experiment. This local phenomenon was accompanied by a significant skin thickening (P≤0.01) since the 12th day (ANOVA, F = 11, 07143, P = 0, 00765) which is confirmed with an inflammatory granuloma in histological study. Hematological analysis and blood chemistry values of the 2 groups showed no significant differences in any of the parameters examined. In summary, PLFO is minimally irritating to the eye and skin after a single exposure, but it may cause irritant contact dermatitis and a reversible thichening of skin after prolonged use. Key words: Pistacia lentiscus, fatty oil, skin, eye, dermatitis, irritation, toxicity.